Molecular characterisation of Galba truncatula, Lymnaea neotropica and L. schirazensis from Cajamarca, Peru and their potential role in transmission of human and animal fascioliasis. - Bargues, M.D. (2012)
Background Human and animal fascioliasis is emerging in many world regions, among which Andean countries constitute the largest regional hot spot and Peru the country presenting more human endemic areas. A survey was undertaken on the lymnaeid snails inhabiting the hyperendemic area of Cajamarca, where human prevalences are the highest known among the areas presenting a "valley transmission pattern", to establish which species are present, genetically characterise their populations by comparison with other human endemic areas, and discuss which ones have transmission capacity and their potential implications with human and animal infection. Methods Therefore, ribosomal DNA ITS-2 and ITS-1, and mitochondrial DNA 16S and cox 1 were sequenced by the dideoxy chain-termination method. Results Results indicate the presence of three, morphologically similar, small lymnaeid species belonging to the Galba/Fossaria group: Galba truncatula, Lymnaea neotropica and L. schirazensis. Only one combined haplotype for each species was found. The ITS-1, 16S and cox 1 haplotypes of G. truncatula are new. No new haplotypes were found in the other two species. This scenario changes previous knowledge, in which only L. viator (= L. viatrix) was mentioned. Galba truncatula appears to be the most abundant, with high population densities and evident anthropophyly including usual presence in human neighbourhood. Infection by Fasciola hepatica larval stages were molecularly confirmed in two populations of this species. The nearness between G. truncatula populations presenting liver fluke infection and both human settings and schools for children, together with the absence of populations of other lymnaeid species in the locality, suggest a direct relationship with human infection. Conclusions The geographical overlap of three lymnaeid species poses problems for epidemiological studies and control action. First, a problem in classifying lymnaeid specimens in both field and laboratory activities, given their transmission capacity differences: G. truncatula mainly involved in transmission to humans, L neotropica typically responsible for livestock infection, and L. schirazensis unable for transmission. Although several phenotypic characteristics may be helpful for a preliminary specimen classification, a definitive classification can only be obtained by marker sequencing. Aditionally, L. schirazensis increases the confusion, owing to its ability to mix with other Galba/Fossaria species and distort fascioliasis data such as transmission capacity and infection susceptibility. Second, a problem for epidemiological analysis, surveillance and control by methods as mathematical modelling and Remote Sensing - Geographical Information Systems. In Cajamarca, low resolution mapping may be insufficient, as already verified in Andean areas where different lymnaeid species overlap.